Spinal Cord Stimulation for Freezing of Gait: From Bench to Bedside - Fonoff, Erich Talamoni; de Lima-Pardini, Andrea C.; Coelho, Daniel Boari; Monaco, Bernardo Assumpção; Machado, Birajara; Pinto de Souza, Carolina; dos Santos Ghilardi, Maria Gabriela; Hamani, Clement (Frontiers in Neurology, 2019)
Spinal cord stimulation (SCS) has been used for the treatment of chronic pain for nearly four decades. With a high degree of efficacy and a low incidence of adverse events, it is now considered to be a suitable therapeutic alternative in most guidelines. Experimental studies suggest that SCS may also be used as a therapy for motor and gait dysfunction in parkinsonian states. The most common and disabling gait dysfunction in patients with Parkinson’s disease (PD) is freezing of gait (FoG). We review the evolution of SCS for gait disorders from bench to bedside and discuss potential mechanisms of action, neural substrates and clinical outcomes.